2023
DOI: 10.1037/tra0001199
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of poor adherence in PTSD treatment from the perspectives of veterans and their therapists.

Abstract: Objective: Dropout rates from trauma-focused PTSD treatments (TFTs) in VA clinics are particularly high. We conducted in-depth qualitative interviews with 29 veterans and their therapists to better understand this phenomenon. Method: Participants were part of a multisite, mixed-methods study of TFT adherence in VA clinics. Veterans were eligible for interviews if they exhibited poor TFT adherence and screened positive for PTSD in follow-up surveys. Interviews were analyzed using qualitative dyadic analysis app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Patients expressed concerns about the potential adverse impact of the treatment on their psychosocial functioning during and after treatment. 52 , 80 , 81 , 92 Patients discussed feeling conflicted about complying with the treatment as this often competed with their on-going “real-world” responsibilities. I felt very overwhelmed, and I felt very lost and very frantic in what I had to do [for therapy].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients expressed concerns about the potential adverse impact of the treatment on their psychosocial functioning during and after treatment. 52 , 80 , 81 , 92 Patients discussed feeling conflicted about complying with the treatment as this often competed with their on-going “real-world” responsibilities. I felt very overwhelmed, and I felt very lost and very frantic in what I had to do [for therapy].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies 50 , 80 , 86 , 87 highlighted the importance of providing psychoeducation regarding PTSD symptoms, the treatment’s rationale, and its expected effects to positive outcomes. I really do not understand CPT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians might partner with patients to manage treatmentrelated distress and jointly explore risk of negative consequences of treatment, as well as possible benefits of treatment despite a potential temporary increase in difficulty, in order to reframe potentially exaggerated expectancies and to prevent negative outcomes from occurring. Clinicians are often unaware of the types of concerns that may contribute to poor outcomes (Meis et al, 2023), so asking patients about their concerns throughout treatment can provide the opportunity to intervene more effectively, whether through problemsolving (Shulman et al, 2019) or another adjunctive procedure, or through bolstering PE or CPT elements (e.g., challenging treatmentinterfering stuck points, empowering patients to engage in exposure) to retain patients in care. Kehle-Forbes et al (2022) reported findings from this sample related to interpretations of ongoing or worsening symptoms as well as concerns about the impact of treatment on functioning.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined beliefs patients reported having in early treatment sessions compared to during active components of treatment. Qualitative research can help to better elucidate the multifaceted processes of treatment engagement and outcomes by allowing us to learn from patients' experiences to identify relevant processes that may not have been previously examined (Meis et al, 2023). Identifying treatment-related beliefs and interpretations occurring during treatment that differentiate treatment discontinuers from completers, and further, PTSD− completers from PTSD+ completers, can help us develop interventions to both keep patients engaged in treatment and ensure they benefit from care.…”
Section: The Present Studymentioning
confidence: 99%